Disability Status, Mortality, and Leading Causes of Death in the United States Community Population. Issue 4 (April 2015) - Forman-Hoffman, Valerie L.; Ault, Kimberly L.; Anderson, Wayne L.; Weiner, Joshua M.; Stevens, Alissa; Campbell, Vincent A.; Armour, Brian S.
Abstract : Objective: We examined the effect of functional disability on all-cause mortality and cause-specific deaths among community-dwelling US adults. Methods: We used data from 142, 636 adults who participated in the 1994–1995 National Health Interview Survey-Disability Supplement eligible for linkage to National Death Index records from 1994 to 2006 to estimate the effects of disability on mortality and leading causes of death. Results: Adults with any disability were more likely to die than adults without disability (19.92% vs. 10.94%; hazard ratio=1.51, 95% confidence interval, 1.45–1.57). This association was statistically significant for most causes of death and for most types of disability studied. The leading cause of death for adults with and without disability differed (heart disease and malignant neoplasms, respectively). Conclusions: Our results suggest that all-cause mortality rates are higher among adults with disabilities than among adults without disabilities and that significant associations exist between several types of disability and cause-specific mortality. Interventions are needed that effectively address the poorer health status of people with disabilities and reduce the risk of death. Abstract : Supplemental Digital Content is available in the text.